2015
DOI: 10.1039/c5tc01464f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of proton irradiation on Si-nanocrystal/SiO2 multilayers: study of photoluminescence and first-principles calculations

Abstract: The investigation of photoluminescence and first-principles calculations clarifies the relationship between the hydrogen passivation of N at the interface and the observed band gap reduction of the embedded Si nanocrystal (NC) for Si NC/SiO2 multilayers containing interfacial nitrogens after proton irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The researchers conducted extensive research on the photoelectronic properties of the bonds of atoms configurated at the interface between Si NC and SiO x . , The Si NC/SiO x interface introduces a local state that can be used as an emission or quenching center to optimize the PLQY and emission range of Si NCs . Therefore, many researchers have studied the interface state formation and photoelectric conversion effects of Si NCs embedded in an oxide matrix by designing surface passivation of Si NCs . As early as 2001, Si NC/SiO 2 core/shell nanostructures were found to oxidate with the addition of nanoparticles in the air, and the band gap of the NCs increased.…”
Section: Silicon Nanocrystal Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers conducted extensive research on the photoelectronic properties of the bonds of atoms configurated at the interface between Si NC and SiO x . , The Si NC/SiO x interface introduces a local state that can be used as an emission or quenching center to optimize the PLQY and emission range of Si NCs . Therefore, many researchers have studied the interface state formation and photoelectric conversion effects of Si NCs embedded in an oxide matrix by designing surface passivation of Si NCs . As early as 2001, Si NC/SiO 2 core/shell nanostructures were found to oxidate with the addition of nanoparticles in the air, and the band gap of the NCs increased.…”
Section: Silicon Nanocrystal Compositesmentioning
confidence: 99%
“…76 Therefore, many researchers have studied the interface state formation and photoelectric conversion effects of Si NCs embedded in an oxide matrix by designing surface passivation of Si NCs. 77 As early as 2001, Si NC/SiO 2 core/ shell nanostructures were found to oxidate with the addition of nanoparticles in the air, and the band gap of the NCs increased. As the time for oxidation of the nanoparticles increased, bandgap changes directly resulted in a blue shift.…”
Section: ■ Silicon Nanocrystal Compositesmentioning
confidence: 99%
“…The quantitative analysis confirms that the CNPs/Si have majority of lattice oxygen in the oxygen deficient region. Figure 3(b) shows the FTIR spectrum of CNPs/Si, which presents the Si-O-Si bending mode and asymmetric stretching mode at ∼807 cm −1 and ∼1093 cm −1 , respectively [27], C-H bonds at 2900-3100 cm −1 , where the carbon is sp 2 and sp 3 hybridized, and C−C, C=C, C=O, C≡C, and aromatic ring bonds at 1200-2170 cm −1 . In addition, O-H groups were observed at 3400-3500 cm −1 .…”
Section: Measurement Of Photovoltaic Propertiesmentioning
confidence: 99%
“…Contrary to the case of porous silicon, this effect in nc-Si/SiO 2 structures was observed after radiation treatment even in the inert gas or in vacuum; hence, it had another nature. Recently, the authors of [11] reported that proton irradiation (the energy 3.5 MeV and the total fluence 10 12 -10 15 cm −2 ) of nc-Si in SiO 2 multilayers leads to significant decrease of the intensity of luminescence centered near 730 nm, and in appearance of the luminescence band near ∼500 nm, assigned to radiative recombination at the radiation induced centers within a-SiO 2 matrix. Larger exposure doses (∼10 6 -10 7 rad), similarly to the case of the porous silicon, led to a partial quenching of PL of the nc-Si/SiO 2 films [10].…”
Section: Introductionmentioning
confidence: 99%